A short segment within the cytoplasmic domain of the neural cell adhesion molecule (N-CAM) is essential for N-CAM-induced NF-κB activity in astrocytes - Little, Edward B. (The National Academy of Sciences, 2001)
The neural cell adhesion molecule (N-CAM) is expressed on the surface of astrocytes, where its homophilic binding leads to the activation of the transcription factor NF-κB. Transfection of astrocytes with a construct encompassing the transmembrane region and the cytoplasmic domain of N-CAM (designated Tm-Cyto, amino acids 685–839 in the full-length molecule) inhibited this activation up to 40%, and inhibited N-CAM-induced translocation of NF-κB to the nucleus. N-CAM also activated NF-κB in astrocytes from N-CAM knockout mice, presumably through binding to a heterophile. This activation, however, was not blocked by Tm-Cyto expression, indicating that the inhibitory effect of the Tm-Cyto construct is specific for cell surface N-CAM. Deletions and point mutations of the cytoplasmic portion of the Tm-Cyto construct indicated that the region between amino acids 780 and 800 were essential for inhibitory activity. This region contains four threonines (788, 793, 794, and 797). Mutation to alanine of T788, T794, or T797, but not T793, abolished inhibitory activity, as did mutation of T788 or T797 to aspartic acid. A Tm-Cyto construct with T794 mutated to aspartic acid retained inhibitory activity but did not itself induce a constitutive NF-κB response. This result suggests that phosphorylation of T794 may be necessary but is not the triggering event. Overall, these findings define a short segment of the N-CAM cytoplasmic domain that is critical for N-CAM-induced activation of NF-κB and may be important in other N-CAM-mediated signaling.